Estágio GO! Uma proposta de jogo de tabuleiro para a pedagogia - COSTA, Tiago Henrique Paixão da (Universidade Federal do Pará, 2024)
The supervised curricular internship, in a school environment, of the Pedagogy course is a stage in which the undergraduate has the opportunity to follow and assist the work of a teacher in the classroom. In this context, joint work and an exchange of knowledge are necessary between all members who are part of the internship journey. According to Raymundo (2013), the internship is a time for socialization and exchange of experiences. However, due to a series of factors, this dialogue and openness are not favored, or are scarce and limited, or restricted to some specific moments. Therefore, this research had the main objective of developing Estágio Go! A board game, with mechanics based on Quests (Howard, 2022) and Roleplaying Games (RPGs), with the aim of facilitating the sharing of knowledge between members of the process. Pedagogy internship in the initial grades of elementary school. Based on the concept of simulated reality (Kapp, 2012), Estágio Go! Proposes an imaginary universe, in which the Pedagogy intern assumes the role of a player and faces a series of situations that could, in fact, happen in the real environment of the internship. . Once faced with these situations or missions, you must use your knowledge and experiences from your undergraduate studies to propose solutions and thus overcome the challenges of the game. This qualitative research was designed as action research and the methodological process was organized as follows: (1) bibliographical study on teacher training, supervised internship, use of games in the context of teaching and creation of board and RPG games; (2) development of the first versions of the board game; (3) testing of game prototypes carried out with students and teachers of the supervised internship discipline in the initial years of Elementary School, of the Full Degree in Pedagogy course at the State University of Pará; and analysis by two experienced school experts; (4) development of the final product Estágio Go! Improved according to the results of field experience and expert evaluation. The results of the investigation showed that the educational product Estágio Go proved to be an aid tool for the internship discipline and was well received by the students and teachers participating in the research.